Impact of wheat globulin addition on dough rheological properties and quality of cooked noodles. (15th November 2021) - Zhang, Li-Li; Guan, Er-Qi; Yang, Yu-Ling; Liu, Yuan-Xiao; Zhang, Ting-Jing; Bian, Ke
Highlights: Functional properties of wheat globulin on dough and cooked noodles were analyzed. Globulin improved the stiffness of dough and the hardness of cooked noodles. Globulin was cross-linked to the gluten molecule mainly by hydrophobic interactions. Globulin affected protein aggregation and conformation following cooking. A model of interaction between globulin and gluten was proposed. Abstract: Impact of globulin addition on the functional and protein structural properties of dough and cooked noodles were investigated. The underlying mechanism was explored through analyzing the interaction between globulin and gluten by using SDS-PAGE, size exclusion chromatography, free sulfhydryl/disulfide bond analysis, laser scanning confocal microscopy and Fourier transform infrared spectroscopy. Results showed that the stiffness/hardness and maximum resistance of dough and cooked noodles were both increased when globulin addition was 1.5% or higher. Besides, extensibility of cooked noodles was also improved when the addition up to 3.0%. The addition of globulin facilitated weakening the S-S bonds in the gluten network and cross-linked with SDS-soluble gluten mainly through non-covalent interactions, especially hydrophobic interactions. Meanwhile, a more rigid protein network structure was observed. Additionally, following cooking, globulin addition accelerated the aggregation of protein molecules. When the addition reached 3%, the protein conformation was transformed from β -sheets and random coils to β -turns.